A Cross-Sectional Investigation of the Importance of Park Features for Promoting Regular Physical Activity in Parks - Costigan, Sarah A. (Int J Environ Res Public Health, 2017)
Introduction: Parks in the US and Australia are generally underutilised, and park visitors typically engage in low levels of physical activity (PA). Better understanding park features that may encourage visitors to be active is important. This study examined the perceived importance of park features for encouraging park-based PA and examined differences by sex, age, parental-status and participation in PA. Methods: Cross-sectional surveys were completed by local residents (n = 2775) living near two parks (2013/2015). Demographic variables, park visitation and leisure-time PA were self-reported, respondents rated the importance of 20 park features for encouraging park-based PA in the next fortnight. Chi-square tests of independence examined differences in importance of park features for PA among sub-groups of local residents (sex, age, parental-status, PA). Results: Park features ranked most important for park-based PA were: well maintained (96.2%), feel safe (95.4%), relaxing atmosphere (91.2%), easy to get to (91.7%), and shady trees (90.3%). All subgroups ranked ‘well maintained’ as most important. Conclusions: Natural and built environment features of parks are important for promoting adults’ park-based PA, and should be considered in park (re)design.